Is Indian automobile industry getting integrated with Asian production network?. (2017) - Nag, Biswajit; De, Debdeep; Singh, Shailendra
Globally, automobile industry is subject to fragmented production system leading to long value chain spreading across the countries. More recently, literature encompasses the issue of international trade, forward and backward linkages, collaboration in R&D, product development and differentiation, etc., leading to a new concept of international production network (IPN). India is now one of the major automobile producers and exporters. In this context, the paper has made an attempt to comprehend India's engagement in IPN and more specifically its participation in ASEAN network. It uses various trade analytic tools such as intra-industry trade, quality margin, participation index, share of foreign value added in exports, sources of foreign value addition, etc. to analyse India's growing competency in the sector.